2021
DOI: 10.1021/acs.jafc.1c04737
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Health-Promoting Effects of Plant MicroRNAs: A Review

Abstract: Plant-derived microRNAs (miRNAs) play a significant role in human health and are “dark nutrients”, as opposed to traditional plant nutrients, as well as important components of food diversification. Studies have revealed that multiple plant-derived miRNA pathways affect human health. First, plant miRNAs regulate plant growth and development and accumulation of metabolites, which alters the food quality and thus indirectly interferes with the health of the host. Moreover, when absorbed in vivo, some miRNAs may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 117 publications
0
23
0
1
Order By: Relevance
“…Combined, these findings suggest that plant miRNAs could exploit some mechanisms to maintain themselves at certain concentrations, laying foundations for their regulatory roles. Zhu et al summarized the recent discoveries that plant miRNAs not only regulate host gene expression by targeting specific mRNAs but also have the potential to maintain the balance among plants, hosts, and host gut microbes . Granted, dietary miRNAs, either from plants or from bovine milk, have to maintain at certain concentrations to function cross-kingdomly. , The minimum thresholds of xenomiRNAs should be investigated in future studies concerning their regulatory effects in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Combined, these findings suggest that plant miRNAs could exploit some mechanisms to maintain themselves at certain concentrations, laying foundations for their regulatory roles. Zhu et al summarized the recent discoveries that plant miRNAs not only regulate host gene expression by targeting specific mRNAs but also have the potential to maintain the balance among plants, hosts, and host gut microbes . Granted, dietary miRNAs, either from plants or from bovine milk, have to maintain at certain concentrations to function cross-kingdomly. , The minimum thresholds of xenomiRNAs should be investigated in future studies concerning their regulatory effects in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the specific mechanisms involved are not yet clear, though it is certain that miRNAs can be taken up and utilized across borders 84 . In addition, plant‐derived miRNAs may regulate host physiological metabolism by targeting intestinal cells or intestinal microorganisms 13 . Although it is not clear whether certain miRNAs can smoothly reach the large intestine through the stomach and small intestine, it is possible to build some particles that can protect miRNAs to reach the large intestine smoothly and thus function as a regulator of intestinal flora 85 .…”
Section: Coarse Grains Regulate Mirnas Expression Profilesmentioning
confidence: 99%
“…12 In addition, plant-derived miRNAs which are also an important component of food diversification, play an important role in human health as 'dark nutrients' as opposed to traditional phytonutrients. 13 MiRNAs are also involved in the regulatory mechanisms of the intestinal flora. A cohort study revealed similar fecal miRNAs expression profiles and intestinal flora features in populations consuming similar dietary components, while results with large differences in dietary components differed significantly, which probably resulted from endogenous/exogenous miRNAs and host-gut microbial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…28 We recently reviewed the nutritional mechanisms of plant-derived miRNA and suggested that miRNAs play a significant role in the cross-kingdom communication of plants, GM, and the host and in maintaining a balance of the three. 29 Recent studies show that the exosome-like nanoparticles (derived from carrot, 30 grapefruit, 31,32 and ginger 30,33 ) can mediate mouse intestinal tissue remodeling, prevent inflammatory bowel disease, and reduce the immune response evoked by intestinal barrier damage. Nanovesicles derived from orange juice can reverse the diet-induced changes in the intestinal tract, reduce triglyceride content, regulate the immune response, improve blood lipid level, and reduce inflammation in gastrointestinal diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, whether it can be delivered to cells remains unclear . We recently reviewed the nutritional mechanisms of plant-derived miRNA and suggested that miRNAs play a significant role in the cross-kingdom communication of plants, GM, and the host and in maintaining a balance of the three . Recent studies show that the exosome-like nanoparticles (derived from carrot, grapefruit, , and ginger , ) can mediate mouse intestinal tissue remodeling, prevent inflammatory bowel disease, and reduce the immune response evoked by intestinal barrier damage.…”
Section: Introductionmentioning
confidence: 99%